Advanced techniques in the production of biochar from lignocellulosic biomass and environmental applications - Farah, Amalina; Abdul Syukor, Abd Razak; Santhana, Krishnan; Haspina, Sulaiman; A. W., Zularisam; Mohd, Nasrullah (Elsevier Ltd., 2022)
Biochar is a carbon-rich product obtained from the thermochemical conversion of biomass. Utilizing biochar is essential for enhancing economic viability and maintaining the ecology effectively. This work reviews the techniques for producing biochar from various lignocellulosic biomass sources. Pyrolysis technology for converting lignocellulosic biomass into biochar has emerged as a frontier research domain for pollutants removal. The effects of biomass feedstock parameters, production techniques, reaction conditions (temperature, heating rate, etc.), activation, and functional group modification are compared on biochar's physical and chemical properties. This review also focused on environmental applications in several domains, such as agriculture and wastewater treatment. Considering the extensive availability of feedstock, excellent physical/chemical surface properties, and inexpensive cost, biochar has a remarkable potential for removing water pollutants efficiently. Studying the evolution properties of biochar by in-situ or post-modification is of great significance for improving the utilization value of lignocellulosic biomass. Biochar is a valuable resource, yet its application necessitates additional research into its properties and structure, as well as the development of techniques to modify those factors.